2022
DOI: 10.1007/s10984-022-09405-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender-sensitive sentiment analysis for estimating the emotional climate in online teacher education

Abstract: Teacher training takes place in distance education to a large extent. Within these contexts, trainers should make use of all the information available to adapt and refine their instructional methods during the training process. Sentiment analysis (SA) can give immediate feedback of the emotions expressed and help in the training process, although it has been used infrequently in educational settings, slow to assess, and bound to interpretative issues, such as gender bias. This research aimed to design and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The vast majority of publications perform SA at word or sentence level (i.e., attributing a sentiment score to each word or sentence and then computing the overall result), but motivation is a particular mental state, directed towards a particular topic, and usually related to behavioral responses. For this reason, we argue that measuring sentiment polarity provides information about the emotional climate of a group or general emotional state of a student (Usart et al, 2022), rather than providing information about a particular mental or emotional state. Hence, attributing polarity results to a mental state may carry the risk of falling into spurious relationships.…”
Section: Measuring Sentimentmentioning
confidence: 99%
“…The vast majority of publications perform SA at word or sentence level (i.e., attributing a sentiment score to each word or sentence and then computing the overall result), but motivation is a particular mental state, directed towards a particular topic, and usually related to behavioral responses. For this reason, we argue that measuring sentiment polarity provides information about the emotional climate of a group or general emotional state of a student (Usart et al, 2022), rather than providing information about a particular mental or emotional state. Hence, attributing polarity results to a mental state may carry the risk of falling into spurious relationships.…”
Section: Measuring Sentimentmentioning
confidence: 99%
“…For example, Guadalupe et al developed SocialMining, a model that uses a Spanish comment corpus to evaluate teacher performance [27]. Mireia Usart et al designed and evaluated a gender-sensitive SA method to characterize the emotional atmosphere of teacher trainees in online courses and improve their learning [28]. Somdeep Das et al investigated the feedback module of an online learning management system (OLMS) and found that combining machine learning algorithms and NLP techniques with OLMS data can improve teaching efficiency [29].…”
Section: Sentiment Analysismentioning
confidence: 99%
“…Supervised Machine Learning Algorithms Articles Decision Tree(DT) [1], [2], [5], [6], [8], [12], [13], [15], [16]], [17], [18], [21], [22], [26], [30], [33], [38], [40], [45], [47], [50],[ Support Vector Machine(SVM) [51], [52], [55], [58], [59], [61], [67], [68], [71], [72], [73],…”
Section: Table (7) Analysis Of Supervised and Unsupervised Machine Le...mentioning
confidence: 99%